Online Audiences and Gatekeeping: User Comments and Their Infuence on Editorial Processes in Newsrooms in Kenya - Oywer, Beryl Anyango; Booker, Nancy; Owilla, Hesbon Hansen; Kimweli, Paul (European Scientific Journal, ESJ, 2023)
In Kenyan newsrooms, there has been a debate about whether to keep the comment section on news websites in the aftermath of Social Media Networks, which allow the media to still collect user opinion without the risk of unregulated third-party comments. This paper sought to establish the nature and influence user comments have on editorial processes as well as explain what value media houses that have retained the comment section are receiving. To investigate this, the researchers adopted mixed methods research approach (quantitative and qualitative) and concurrent mixed methods research designs. The targeted population was journalists working in media houses that operate in print, broadcast, and digital news website in Nairobi County. The targeted media houses were: Nation Media Group (NMG), Standard Group (SG), and Radio Africa Group (RAG). Sample size comprised of 252 participants for quantitative data, 9 key informants for in-depth interviews, and 84 articles for direct content analysis. Survey and directed content analysis were used as strategies of inquiry. These strategies were aided by questionnaires, in – depth interviews, and code sheet as data generation tools. Statistical Package for Social Sciences (IBM/SPSS) was used to analyse quantitative data. Quantitative data was presented using tables and pie-charts. Qualitative data was thematically analysed and presented in form of themes. The findings show that, contrary to popular belief, discussions in news website comment sections are frequently marred by incivility. Instead, the majority of the comments were deliberative in nature, with audience members just looking for a forum to express themselves in a civil manner. However, in cases where there were reported incidences of incivility, the sources quoted were the main trigger. Journalists have been shown to use user input in the comment section to gauge the quality of the content they produce, while media companies use audience knowledge to make strategic decisions. The results shed light on how newsrooms may give the public a platform to discuss and give their input on the news and still maintain deliberative debates.